Determinasi Lingkungan dan Perilaku terhadap Keberadaan Jentik Aedes spp: Environmental and Behavioral Determinants of the Presence of Aedes spp - Chahaya, Indra; Tumanggor, Winni R.E.; Sutami, Baiq Dian; Tsabitha, Adinda (Poltekes Kemenkes Tanjungpinang, 2025)
The high cases of DHF highlights the importance of identifying factors that contribute to the breeding of mosquito larvae. This study aims to examine the relationship between environmental conditions and human behavior related to the presence of Aedes spp larvae. A quantitative research method with an analytical approach and a cross-sectional design was used. The sample consisted of 150 households in the Baru Ladang Bambu Subdistrict, Medan Tuntungan District, Medan City. The results indicate that the habit of hanging clothes is significantly associated with the presence of Aedes larvae (p-value = 0.010). Other variables such as house type, occupancy density, ventilation, wire screens, opening ventilation, clutter, closing and draining landfills, burying used items, using abate powder, keeping larva-eating fish, and receiving fogging showed no significant relationship. In conclusion, the main risk factor identified is the indoor practice of hanging clothes. Based on these findings, it is recommended that mosquito control programs be enhanced through educational efforts, focusing on changing community behavior particularly discouraging the habit of hanging clothes indoors—as a preventive measure to reduce the presence of Aedes spp larvae.